2020
DOI: 10.1080/10474412.2020.1819298
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Consultation in Schools: A Systematic Review and Call for Restorative Justice Science to Promote Anti-Racism and Social Justice

Abstract: Restorative justice practices (RJP) in schools is an increasingly popular approach to responding to discipline showing modest effectiveness. However, there is little research within the school consultation literature that examines the use of RJP. In over a decade, there have been only six studies. These studies are reviewed and directions for future research are discussed. Over the next 30 years, researchers need to pursue restorative justice science with a social justice vision focusing on restorative consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…From the studies examined, results of great interest emerged regarding the benefits of applying restorative justice and practices in schools, as also confirmed by the theoretical articles and reviews reported in the Appendix A [ 57 , 58 , 59 , 60 , 61 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. However, there is still limited evidence in terms of direct correlation, which suggests further studies.…”
Section: Discussionmentioning
confidence: 70%
“…From the studies examined, results of great interest emerged regarding the benefits of applying restorative justice and practices in schools, as also confirmed by the theoretical articles and reviews reported in the Appendix A [ 57 , 58 , 59 , 60 , 61 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. However, there is still limited evidence in terms of direct correlation, which suggests further studies.…”
Section: Discussionmentioning
confidence: 70%
“…Watching racialized violence particularly harms people of color (Bor et al., 2018), so institutional agents should not re‐expose individuals of color to such incidents and should consider providing additional support, such as counseling or other supportive services, to individuals of color during such times (Galán et al., 2021). More generally, adults should take care to provide educational opportunities that help students cope with challenges, such as social‐emotional learning curricula, restorative justice practices (Song et al., 2020; Song & Swearer, 2016; Wenzel et al., 2008), and belonging interventions (Walton & Cohen, 2007; 2011) are options that can be explored.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…At the school policy level, schools should analyze their policies through a racial justice lens, specifically reviewing opportunity, support, and discipline as locations of inequity and injustice. Schools should shift toward restorative justice (Song et al 2020). Schools should also partner with the families and communities they serve to promote children's antiracist learning.…”
Section: Summary and Future Directions For Change Toward Antiracismmentioning
confidence: 99%